17 wrzesnia 1939 roku slonce zgaslo nad Horyniem : wspomnienia lwowskiego kadeta - Petkowski, Jozef (Niepokalanow : [s.n.], 1998)
The personal narative of a Polish lieutenant and his experiences and capture in the first days of WW II on the Eastern frontier of Poland.
Keywords: Petkowski, Jozef; Germany. -- 1939 Aug. 23.; World War, 1939-1945 -- Personal narratives, Polish